2021
DOI: 10.1186/s43088-021-00122-x
|View full text |Cite
|
Sign up to set email alerts
|

Entomological survey for identification of Aedes larval breeding sites and their distribution in Chattogram, Bangladesh

Abstract: Background Studying the characteristics of Aedes mosquito habitats is essential to control the mosquito population. The objective of this study was to identify the breeding sites of Aedes larvae and their distribution in Chattogram, Bangladesh. We conducted an entomological survey in 12 different sub-districts (Thana) under Chattogram City, during the late monsoon (August to November) 2019. The presence of different wet containers along with their characteristics and immature mosquitoes was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…On the other hand, housewives were at a higher risk of infection (OR= 2.29) although the relation was nonsignificant. It indicates that house status and environment play a role in dengue transmission may be due to the presence of Aedes mosquito larvae and breeding sites in and around the houses of the study area found by an entomological survey (Rahman et al 2021). On the other hand, government employees and students were significantly associated with protection against dengue virus infection.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…On the other hand, housewives were at a higher risk of infection (OR= 2.29) although the relation was nonsignificant. It indicates that house status and environment play a role in dengue transmission may be due to the presence of Aedes mosquito larvae and breeding sites in and around the houses of the study area found by an entomological survey (Rahman et al 2021). On the other hand, government employees and students were significantly associated with protection against dengue virus infection.…”
Section: Resultsmentioning
confidence: 81%
“…The copyright holder for this preprint this version posted August 26, 2021. ; https://doi.org/10.1101/2021.08.24.21262563 doi: medRxiv preprint et al 2015b). Single houses presented higher odds (2.49) for the infection of occupants which may be due to high densities of Aedes larvae recorded in single independent houses of the study area (Rahman et al 2021). Single houses are small building or semi paka structure inhabitants of one or two families.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations